Caring for the Patient with Breast Cancer - Nathanson, S. (1976)
The management of the patient with cancer of the breast is a challenge to the family physician. Foremost is the need to educate the patient about self-examination and the physician's role in providing a thorough clinical evaluation and the appropriate use of mammography. Once a diagnosis is established the patient requires counselling and referral to the needed specialists. Finally, the family physician is in a key position to coordinate the necessary services, provide access to rehabilitation programs and offer the necessary psychological support to the patient and her family.